A Bibliometric Analysis of Research on Industrial Clusters and Digitalization - Günay, Abdullah; Çopuroğlu, Cemalettin (Siirt University, 2024)
The technological change created by digital technologies is encountered in industrial clusters as in all areas of life. Although industrial cluster studies on digitalization and virtualization are limited, they have become popular in the last few years. In this context, the aim of this study is to review the studies that include the concepts of “industrial clustering” and “digital/virtual” and to determine the topics and trends that have intensified over the years. In the study, 137 studies related to “digital”, “virtual” and “industrial clustering” obtained from the Web of Science database were subjected to co-authorship analysis, source citation analysis, country-based citation analysis, keyword analysis and bibliographic mapping analysis through VOSviewer visualization tools. This bibliographic mapping shows the contributions of authors and countries as well as their collaboration over time. The bibliometric analysis also revealed emerging areas, topics and trends in this research area. The findings of the study are expected to contribute to academics who will conduct future studies on industrial clustering in terms of identifying academic resources and observing trends over the years.

Dijital teknolojilerin yarattığı teknolojik değişim hayatın her alanında olduğu gibi endüstriyel kümelerde de karşımıza çıkmaktadır. Dijitalleşme ve sanallaşma ile ilgili endüstriyel kümelenme çalışmaları sınırlı olsa da son birkaç yıldır popüler hale gelmeye başlamıştır. Bu bağlamda çalışmanın amacı “endüstriyel kümelenme” ile “dijital/sanal” kavramlarının yer aldığı çalışmaların taranması ve yıllara göre yoğunlaşan konuların ve eğilimlerin belirlenmesidir. Çalışmada Web of Science veri tabanından elde edilen “dijital”, “sanal” ve “endüstriyel kümelenme” ile ilgili 137 çalışma, VOSviewer görselleştirme araçları aracılığıyla ortak yazarlık analizi, kaynak atıf analizi, ülke bazında atıf analizi, anahtar sözcük analizi ve bibliyografik eşleştirme analizi gerçekleşmiştir. Bu bibliyografik haritalama, yazarların ve ülkelerin katkılarının yanı sıra zaman içindeki işbirliğini göstermektedir. Ayrıca bibliyometrik analiz aynı zamanda bu araştırma alanında ortaya çıkan alanları, konuları ve eğilimleri de ortaya çıkarmıştır. Araştırmanın bulguları, ileride endüstriyel kümelenme ile ilgili çalışma yapacak akademisyenlere akademik kaynakların tespiti ve yıllara göre eğilimlerin gözlenmesi konusunda katkı sağlayacağı düşünülmektedir.
Endüstriyel Kümelenmeler ve Dijitalleşme Üzerine Araştırmalar Hakkında Bibliyometrik Bir Analiz
Keywords: Management Information Systems; Yönetim Bilişim Sistemleri; Information Systems (Other); Bilgi Sistemleri (Diğer)